Elvis and the tropical double trouble - Webb, Peggy (Webb, Peggy. Southern cousins mystery., 2011)
"It's two times the turmoil for mayhem magnet Callie, her curvaceous cousin Lovie, and Elvis, the King reincarnated as nothin' but a hound dog. This time they're finding a lot more than relics on an archeological dig that could truly be their ruin....Forced to choose between one man who wants to marry her and another who already did, Callie Valentine Jones can't think of a better way to check out of her personal Heartbreak Hotel then to get way, way out of town. So when Lovie invites the whole Valentine clan to visit her brainy new beau's worksite near Cozumel, Callie packs up her crooning basset hound and heads straight for the airport --- But the moment they arrive at the dig, Elvis sniffs out T-R-O-U-B-L-E, in the form of a skeleton too fresh to be part of the research and too dead to spell anything but homicide. Suspicious minds blame ghosts and gods, but Callie knows the guilty party is all too human --- and for once, she's determined not to get involved. That determination goes right out the window when Lovie and Elvis go missing. It's now or never, if Callie wants to save her cousin and her canine from someone who's got murder always on his mind. And when her sexy ex arrives to save the day, she'll have to keep her head together, because her love won't wait --- but neither will a killer with something deadly to hide."--P. [4] of cover.